The (Option-) Value of Overstaying - Romuald Méango; François Poinas (Center for Economic Studies and ifo Institute (CESifo), 2023)
The paper is structured around three main contributions. First, it takes advantage of a unique survey on Afghan asylum seekers in Germany to provide novel descriptive insights into asylum seekers' beliefs about their outcomes and the associated intention to overstay. Second, it estimates asylum seekers' perceived ex ante returns on overstaying, and option values of regularisation, deportation, and experimentation. Third, it assesses and rejects the cost-effectiveness argument for assisted voluntary return policies. Instead, it estimates a sizeable willingness-to-pay of asylum seekers for investments that would guarantee their regularisation.
Keywords: C20; D84; F22; J15; J18; J61; O15; 330; subjective expectations; intention to overstay; asylum seekers; Germany; Afghanistan